Prevention of Pathogenesis of Infection in Postpartum Women Through Postpartum Care Culture - Ita Herawati; Heni Hidayani; Mifatkhul Jannah; Nova Marlen Tohatta; Ritha Merren; Sulastri Tattoo; Yessika Putri (Jurnal Penelitian Pendidikan IPA, 2024)
Cultural beliefs and practices significantly influence postpartum care, affecting maternal health outcomes both positively and negatively. In developing countries, around 70% of postpartum mothers lack adequate care and often only seek medical attention in severe cases, contributing to elevated maternal mortality rates during the postpartum period. This study investigates how cultural practices impact postpartum care and the incidence of postpartum infection pathogenesis. Using a cross-sectional study design, the research analyzed data from 141 participants with chi-square tests. Results reveal a significant relationship between postpartum care culture and infection incidence, with a p-value of 0.000. Participants were primarily aged 20-35 years (61%), had high school education (68.80%), and were non-working (72.30%). These factors suggest that education and employment status may affect postpartum care practices. A majority of respondents exhibited positive care practices, with 51.10% reporting good care and no postpartum infections. The findings highlight the necessity for developing culturally sensitive postpartum care guidelines to reduce infection risks and enhance maternal health outcomes by incorporating local cultural values into care practices.